Iodine-mediated new strategy for the synthesis of 2, 5-disubstituted oxazoles from methyl ketones and TosMIC. Issue 15 (3rd August 2018) - Pogaku, Naresh; Krishna, Palakodety Radha; Prapurna, Y. Lakshmi
Abstract: A new strategy has been developed for the construction of oxazoles from methyl ketones and TosMIC via self-sorting oxidative domino reaction strategy. In contrast to its usual reactivity as C–N≡C synthon in the synthesis of oxazoles, TosMIC was utilized as ammonium surrogate in the present method. The protocol is attractive in terms of readily available starting materials, metal and base free conditions, operational simplicity, C–N and C–O bond formation. A variety of 2, 5-disubstituted oxazoles were prepared in moderate-to-good yields. Graphical Abstract: